103k views
2 votes
Solve the equation for x 3x+9x = 6x + 42

User Greg Ennis
by
5.1k points

1 Answer

2 votes

= 3x + 9x = 6x + 42

= 3x + 9x - 6x = 42 ( transposing +6x from LHS to RHS changes +6x to -6x )

= 12x - 6x = 42

= 6x = 42

= x = 42 ÷ 6 ( transposing ×6 from LHS to RHS changes ×6 to ÷6 )

= x = 7

Let us check whether we have found out the correct value of x or not by placing 7 in the place of x :

= ( 3 × 7 ) + ( 9 × 7 ) = 6 × 7 + 42

= 21 + 63 = 42 + 42

= 84 = 84

= LHS = RHS

Hence proved we have derived the correct value of x .

Therefore , the value of x = 7 .

User RaviRokkam
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.